Exploring the effect of napping on sleep quality and duration in collegiate athletes. Issue 5 (22nd June 2022) - Stephenson, Katie L.; Trbovich, Alicia M.; Vandermark, Lesley W.; McDermott, Brendon P.; Henry, Luke C.; Anderson, Morgan N.; Elbin, R. J.
Abstract: Purpose: The purpose of this study was to extend research on napping and sleep behaviors in collegiate athletes, and to compare nappers and non-nappers on sleep quality and duration. Methods: Current varsity, club, and intramural athletes between 18-29 years completed the Short Napping Behavior Scale, Pittsburgh Quality Sleep Index, Generalized Anxiety Disorder-7, and the Patient Health Questionnaire-9. Results: Approximately 72% (129/179) reported napping. There were no significant differences in outcomes between nap frequency groups on sleep quality ( Χ 2 (3)=4.97, p =.17) or duration ( Χ 2 (3)=1.20, p =.75). Moreover, there was no significant differences for nap length groups on sleep quality ( Χ 2 (3)=7.03, p =.07) or duration ( Χ 2 (3)=1.32, p =.72). Furthermore, there were no significant differences for nap timing groups on sleep quality ( Χ 2 (3)=1.54, p =.67) or duration ( Χ 2 (3)=2.43, p =.49). Conclusion: In a sample of collegiate athletes, nap frequency, length, and timing were not associated with worse sleep quality or duration.